2022
DOI: 10.1108/arch-11-2021-0321
|View full text |Cite
|
Sign up to set email alerts
|

Sensory spaces: sensory living – studio teaching the design of autism-friendly adult accommodation

Abstract: PurposeThe study aims to evaluate: (1) How university students from interior architecture can create a forward-looking “Sensory Living” brief informed by both external autism experts and a specialist tutor, evidenced through Leeds City Council's live autism adult accommodation project. (2) Issues involved with moving an experimental studio teaching model online during the COVID-19 pandemic.Design/methodology/approachA grounded theory approach informs an innovative teaching model, run over two years, to create … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…A significant instance of pervasive development being witnessed throughout the globe is the complex neurodevelopment condition called autism spectrum disorder (ASD) which impacts behavior, communication, and social interaction (1)(2)(3)(4). The scientific community has conducted several research studies in recent years to assess the incidence and prevalence of ASD (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…A significant instance of pervasive development being witnessed throughout the globe is the complex neurodevelopment condition called autism spectrum disorder (ASD) which impacts behavior, communication, and social interaction (1)(2)(3)(4). The scientific community has conducted several research studies in recent years to assess the incidence and prevalence of ASD (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, architects and designers must prioritize the integration of natural environments in building design to create healthier and more sustainable spaces for occupants, including sensory gardens and other natural sensory networks embedded as part of the sensory escape network. [3] [18]…”
Section: Natural Elements and Design Integration In Open Spacesmentioning
confidence: 99%
“…A K-12 study found that decibel levels below 55 dB reduce distress in autistic students, while distress behaviors increase at 55-70 dB, marking the first empirical research on specific decibel levels for learning environments and autistic comfort. Fig (3) shows the Noise Level Decibels Chart. [23,24] Master planning involves identifying low-stimulus zones, particularly in learning environments, away from noise sources.…”
Section: The Six Feelings Frameworkmentioning
confidence: 99%
See 1 more Smart Citation